PENGARUH INTELLECTUAL CAPITAL DAN RATA – RATA PERTUMBUHANNYA (ROGIC) TERHADAP KINERJA BANK SYARIAH BERDASARKAN ISLAMICITY PERFORMANCE INDEX DI INDONESIA - Rani, Sasiska; Rianty N, Martha (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
This study examines the effect of intellectual capital and the average growth intellectual capital (ROGIC) on the performance of Syariah Banks based on the Islamicity Performance Index in Indonesia. The Islamicity Performance Index in this study is proxied by the Profit Sharing Ratio (PSR). The sample obtained was based on the purposive sampling technique in this study, namely 10 Syairah Banks from 2015 - 2019. This study used data analysis techniques in the form of multiple regression analysis. The results show that there is a negative effect between intellectual capital on the Islamicity Performance Index, which is proxied by the Profit Sharing Ratio (PSR). The average growth of intellectual capital (ROGIC) has a positive effect on the Islamicity Performance Index, which is proxied by the Profit Sharing Ratio (PSR).